ロコモティブシンドロームの自覚に対する日常生活の工夫 - 河相 てる美; 宮城 和美; 境 美代子; 小出 えり子; 金森 昌彦 (日本看護研究学会雑誌, 2018)
Purpose: The purpose of this study was to identify the relationship between the awareness of locomotive syndrome and daily life in elderly individuals living independently in the community. Method: We conducted semi-structured interviews with seven elderly individuals, and utilized the KJ method to summarize the ideas. Results: The affinity diagram revealed that subjects became aware of locomotive syndrome which made them feel anxious about their future, and prompted them to become responsible for aging, try preventing falling themselves, and adjust daily life for exercise. Awareness of locomotive syndrome precipitated two different feelings. Conclusion: Subjects' attitudes after realizing that they had developed locomotive syndrome were categorized into two types: Feeling anxious about their future, but being unable to take action; or becoming responsible for aging, maintaining a good relationship with their families and people in the community, and trying to prevent falling by themselves. These results suggested the need for healthcare professionals to provide support for elderly individuals that includes regular daily exercise, based on their feelings and issues in general. 目的：地域在住高齢者の「ロコモ」に対する自覚と日常生活の工夫を構造化する。方法：高齢者７人を対象とし，半構造化インタビューをもとにKJ法を用いた。結果：「地域在住高齢者のロコモティブシンドロームを自覚した日常生活の工夫」の図解は，【身体機能の低下の実感】が，【先行き不安】を感じる方向と【「老い」の役割意識】をもち【自覚的な転倒予防】を行い，さらに【「運動」を意識した日常生活の工夫】につながってゆく方向とに影響を与え，二方向に分極している状況が示された。結論：「ロコモ」の実感より，先行きの不安を感じながらも対策を講じることができないでいるのか，責任のある老い方を意識し，社会や家族との関係を維持しながら，自覚的に転倒予防に努めようとするのか，二方向を示している。老年期の普遍的な葛藤・課題を視野に入れつつ，継続した運動が日常生活に取り込まれるよう支援する必要性が示唆された。